The economic consequences of voluntary environmental reporting on shareholder wealth / Ruslaina Yusoff, Shariful Amran Abd Rahman and Wan Nazihah Wan Mohamed - Yusoff, Ruslaina; Abd Rahman, Shariful Amran; Wan Mohamed, Wan Nazihah (Institute of Research, Development and Commercialization (IRDC), 2006)
This study was carried out to examine the economic consequences ofvoluntary environmental reporting on shareholders' wealth among Malaysian Listed Companies that voluntarily disclosed environmental information in their financial report. One hundred andfifty two (152) companies of Bursa Malaysia (MSE) had been identified as a sample in the current study. Seventy six (76) companies were classified as environmental reporting companies while the remaining companies were classified as non-environmental reporting companies. The classification was done in order to determine the differences between share price, profitability and market equity for both types of companies. The study hypothesizes that voluntary environmental reporting leads to an improvement in the shareholders wealth. However, the results show that there is no significant difference between cumulative abnormal return for environmental and non-environmental reporting companies. Based on the results obtained, it can also be concluded that profitability and size of the companies do not have any significant roles in deciding whether or not to produce environmental reporting companies.